Proteomics related to the biocontrol of Pythium damping off in maize with Trichoderma harzianum - CHEN Jie; Gary G Harman; Alfio Comis (浙江大学学报. 农业与生命科学版, 2004)
Trichoderma harzianum strain T22 controls various diseases of maize and other crops, including seedling and root rots caused by Pythium ultimum. Seedlings of inbred line Mo17 were grown from T22-treated or untreated seeds in field soil or in field soil intested with the pathogen. Five days after planting, seedlings of Mo17 (5-days-old) were smaller in the presence of P. ultimum and larger in the presence of T22 relative to the control. The combination of T22 with P. ultimum (T22+P. ultimum) resulted in plants as large as T22 alone. Methods for protein extraction and 2-D gel electrophoresis were developed. Proteins in seedlings roots from the various treatments were separated on 2-D gels and analyzed using PDQuest™ 2-D software. With seedlings produced from T22-treated seeds, there were 104 unmatched proteins and 164 matched proteins relative to the control, and 97 and 150 from the treatment with T22+P. ultimum, respectively, however, with P. ultimum alone the numbers were much lower than above two treatments. Comparatively, there was very lower similarity of proteome patterns of seedling roots with T22 or P. ultimum or both to control seedlings, the correlative coefficient values were 0.72, 0.51 and 0.49 for the comparisons among control with T22, P. ultimum and T22+ P. ultimum, respectively. Moreover, correlative coefficient of proteome patterns between T22 with P. ultimum was only 0.65, and T22 fungal proteome were also not same as any one of seedling roots with various treatments. Taken together, the components in seedling root proteome seemed to be mostly coming from Mo17 plants themselves and affected strongly by either microbes, but the effects appeared to be stronger by P. ultimum than by T22.41 spots were selected for protein mass fingerprinting identification, and most detected-spots were intensified in abundance by T22 or T22+ P. ultimum treatments such as pathogenesis-related protein and endochitnase etc. SOD (Mn) was found to be involved in the defensive reaction of host against P. ultimum because the protein only appeared in the treatment with T22 or T22+ P. ultimum. Besides, some proteins associated with host respiration, nutrition synthesis and transport appeared to be in coordination with defensive-related proteins against the damping off.